2005
DOI: 10.1038/nri1592
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells as therapeutic vaccines against cancer

Abstract: Mouse studies have shown that the immune system can reject tumours, and the identification of tumour antigens that can be recognized by human T cells has facilitated the development of immunotherapy protocols. Vaccines against cancer aim to induce tumour-specific effector T cells that can reduce the tumour mass, as well as tumour-specific memory T cells that can control tumour relapse. Owing to their capacity to regulate T-cell immunity, dendritic cells are increasingly used as adjuvants for vaccination, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
906
2
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,076 publications
(918 citation statements)
references
References 139 publications
6
906
2
4
Order By: Relevance
“…DCs play a fundamental role in the induction of adaptive immune responses as well as in the maintenance of peripheral tolerance [1][2][3]. Through the expression of pattern-recognition receptors (PPRs) such as Toll-like receptors (TLRs), DCs are able to sense a wide array of pathogens and mount an appropriate T-helper (Th) cell response [4].…”
Section: Introductionmentioning
confidence: 99%
“…DCs play a fundamental role in the induction of adaptive immune responses as well as in the maintenance of peripheral tolerance [1][2][3]. Through the expression of pattern-recognition receptors (PPRs) such as Toll-like receptors (TLRs), DCs are able to sense a wide array of pathogens and mount an appropriate T-helper (Th) cell response [4].…”
Section: Introductionmentioning
confidence: 99%
“…At the level of cellular gene therapy, IL-4-expressing transduced T cells [26,27] or dendritic cells (DCs) [28] have been used with some success. Unlike antigen-specific and/or regulatory T cells, autologous DCs are easy to generate and have been safely used in numerous human clinical trials for therapeutic vaccination against cancer [29] and chronic viral infections [30]. Because of their ability to migrate to selective tissues and lymph nodes to regulate immune responses, DCs represent an attractive cellular candidate to be used in adoptive cellular therapy of autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…DCs have attracted much interest during the past decades for their use in therapeutic vaccination against cancer, owing to their professional antigen‐specific T cell immunity. Clinical trials have shown that the use of tumour antigen‐loaded DCs in cancer patients is safe; however, their potential in inducing anti‐tumour immunity to eradicate tumours is seen in only a minority of patients 1, 2. This underscores the necessity to redesign and optimize current procedures for DC vaccine manufacture.…”
Section: Introductionmentioning
confidence: 99%